Learner Autonomy: Iraqi EFL Teachers’ Beliefs - Alzeebaree, Yaseen; Yavuz, Mehmet (European Scientific Journal, ESJ, 2016)
Today students need to take responsibility for their own learning and be autonomous more than thirty years ago. Learner autonomy, which makes the learners more effective, has been given attention in the language learning process over the last three decades. The goal of this study is to explore Iraqi English teachers’ beliefs about learner autonomy. The participants of the study consist of 116 EFL teachers (87 males and 29 females) from different academic (Diploma, Bachelor, Master and PhD) and teaching (intermediate, secondary and university) levels. A questionnaire developed by Borg & AlBusaidi (2012) is used to elicit the required data. Data is analyzed by using SPSS version 22. The results of the study reveal that EFL teachers have a positive attitude to some extent towards learner autonomy. The results of the study and their pedagogical implications are discussed, and recommendations for further research are provided.